Quality-satisfaction-loyalty: consumer behaviour in catering - Rudolfné Katona, Mária; Komáromi, Nándor (Applied Studies in Agribusiness and Commerce, 2014)
Our study is the result of the initial research of a qualitative and quantitative research consisting of more stages. The survey was made between 2007 and 2013 and specially focused on the satisfaction of Hungarian customers of catering enterprises with hot kitchen as well as on factors influencing satisfaction and customer loyalty. The results proved that a well planned, central strategy cannot be prepared for the whole catering industry as even enterprises with the same profile (warm food kitchen) show significant differences. The most important task for an enterprise is to establish and know its appropriate clientele well in order to suit its services, selection to their requirements. Our assumption that customers of fast food restaurants, canteens have lower expectations from selection, personal relations, quality of services than customers of restaurants, public houses, wayside inns, brasseries with traditional methods of selling was proven. In the lattest, the main aspect of choosing a 'favourite place' was the quality of human relations, with the special role, besides other customers, of the staff. Establishing unique atmosphere to the liking of customers can be regarded as an important point of the operational strategy. It was also proven that the majority of regular customers of restaurants are men, coming from the economically active population. Other active users are youngsters, they mainly go to fast food restaurants. More impersonal advertisements hardly have any effect, while successful word of mouth propaganda can be achieved by consequent, high level work. Regular customers can be characterized by rather emotional than market-based attachment. Favourite units are mainly preferred because of their atmosphere, relationships with acquaintances and friends, not because of measurable features, selection or prices. Those visiting catering enterprises with hot kitchen more frequently are more critical and less satisfied, in spite of this, they are reluctant to part from their regular places.